Influence of Azospirillum brasilense associated with silicon and nitrogen fertilization on macronutrient contents in corn - Galindo, Fernando Shintate [UNESP]; Minhoto Teixeira Filho, Marcelo Carvalho [UNESP]; Buzetti, Salatier [UNESP]; Rodrigues, Willian Lima [UNESP]; Fernandes, Guilherme Carlos [UNESP]; Marcandalli Boleta, Eduardo Henrique [UNESP]; Barco Neto, Mauricio [UNESP]; Azambuja Pereira, Maikon Richer de [UNESP]; Leonel Rosa, Poliana Aparecida [UNESP]; Pereira, Ingrid Torres [UNESP]; Gaspareto, Rafaela Neris [UNESP] (De Gruyter Poland Sp Z O O, 2020)
Information regarding the interaction between biological nitrogen fixation (BNF) with Azospirillum brasilense inoculation and the use of silicon (Si) is needed. Silicon exerts numerous benefits on grasses, especially when the plants are subjected to biotic and abiotic stresses, affecting plant nutrition. The aim of this research was to determine if there is a synergistic effect between the inoculation with A. brasilense and Si use, on macronutrient content in corn shoot and root. The field trial was performed in Selviria, Brazil, on a Typic Rhodic Hapludox soil under no-till system. The experimental design was a completely randomized block design with four replicates arranged in a 2 x 5 x 2 triple factorial arrangement, consisting of two soil acidity corrective sources (dolomitic limestone and Ca and Mg silicate as sources of Si); five N doses (0, 50, 100, 150 and 200 kg ha(-1) applied in topdressing); with and without seed inoculation with A. brasilense. The inoculation favored N concentration in shoots and increased the N and S concentration even when associated to high N rates in topdressing. The Si as Ca and Mg silicate associated with the increment of N rates does not promote an increase in the macronutrients uptake. Although it did not favor the N use, the Si also did not negatively affect the benefits of the A. brasilense.
Keywords: Nutritional evaluations; Biological nitrogen fixation in grasses; Plant growth promoting bacteria; Silicon use; Nitrogen fertilization management; Zea mays L.